Aloplastické materiály z pohledu jejich citlivosti ke kolonizaci bakteriemi - Ballay, R; Landor, I; Růžička, F; Melicherčík, P; Tomaides, J; Jahoda, D (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2016)
UNLABELLED: PURPOSE OF THE STUDY The alloplastic materials currently used for protective surface layers on implants were tested in vitro under microbiological laboratory conditions by contamination with microbial agents most frequently found in deep infection of total joint replacements. The objective was to find out how the resistance to bacterial colonisation was related to different surface finishes. MATERIAL AND METHODS Each of 14 samples of alloplastic material currently used in the manufacture of orthopaedic implants was inoculated with each of the group of microorganisms most frequently infecting joint replacements; these were Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, Enterococcus faecalis and Escherichia coli. At 24 hours of incubation, biofilms produced on sample surfaces were collected, stained with crystalline violet and assessed by spectrophotometry. The average value of biofilm absorbances (AV595) for the group of microorganism tested was taken as a basic characteristic of each material sample indicating its sensitivity to bacterial. RESULTS Of the metal materials with smooth surface finish, Vitalium (AV595, 0.368) showed the lowest affinity to microbial colonisation; next was titanium (AV595, 0.459) and steel (AV595, 0.505). A significant increase in sensitivity to bacterial colonisation was recorded in all types of surface finish of steel (AV595, 0.571) and in titanium alloy with a rough surface texture (AV595, 0.737 to 1.676); p < 0.05. Porous titanium surfaces significantly increased material affinity to colonisation. DISCUSSION Our study had certain limitations concerning in vitro evaluation of porous surfaces that have high affinity to bacterial colonisation. Porous titanium, and its hydroxyapatite layer in particular, considerably promotes osteoblast colonisation of the surface as well as implant osseointegration in the bone bed. Microorganisms therefore have no room for surface colonisation. Problematic may remain the surface parts outside contact with bone that keep their affinity to bacterial colonisation. CONCLUSIONS The material of choice for cemented implants is Vitalium which, of all metal surfaces, has the lowest sensitivity to bacterial colonisation. The materials of choice for cementless implants are titanium alloys. However, an osteoactive surface not in contact with bone remains a problem. On the one hand, its roughness and porosity are crucial to good osseointegration, on the other hand, its affinity to bacterial colonisation is high. KEY WORDS: alloplastic material, biofilm, joint replacement infection.
Keywords: Escherichia coli; biokompatibilní materiály; Arthroplasty, Replacement; Prostheses and Implants; infekce spojené s protézou; povrchové vlastnosti; artroplastiky kloubů; Vitallium; lidé; Titanium; Prosthesis-Related Infections; Staphylococcus epidermidis; titan; Staphylococcus aureus; Biocompatible Materials; Materials Testing; Pseudomonas aeruginosa; vitalium; testování materiálů; Enterococcus faecalis; protézy a implantáty; biofilmy; Biofilms; Surface Properties; Humans